Laryngeal replacement with an artificial larynx after total laryngectomy: The possibility of restoring larynx functionality in the future. Issue 11 (21st June 2014) - Debry, Christian; Dupret–Bories, Agnes; Vrana, Nihal E.; Hemar, Patrick; Lavalle, Philippe; Schultz, Philippe
Abstract Background Most patients perceive total laryngectomy as a mutilation carrying with it a loss of physical and psychological integrity. Thus, an artificial larynx system that can replace the laryngeal functions would significantly improve the quality of life for the afflicted patients. Methods This report, with accompanying video, presents the first case in an ongoing clinical trial of laryngeal rehabilitation using an artificial larynx after total laryngectomy for squamous cell carcinoma, for an 8‐month follow‐up period. We depict the prosthesis' features, our 2‐step surgical procedure, and the outcome. The prosthesis is formed of 2 parts: (1) a tracheal prosthesis with a porous titanium junction with trachea, which was implanted in the first step to ensure its colonization, and (2) a removable part composed of concentric valves that enable inhalation and exhalation. The second part was implanted endoscopically. The implant was monitored with a retrograde nasofibroscopy of the tracheal prosthesis lumen and CT scans over a course of 8 months. Results The patient's functioning in the relevant postoperative problem areas, such as swallowing, breathing, and smelling, has significantly improved. The patient was able to talk in a whispering fashion while the tracheostomy was temporarily closed. The implant's porous part was in the process of being colonized by the surrounding tissue and no fistulas were observed as evidenced by barium swallow. Conclusion As the current case shows, tracheotomy closure can be performed, and laryngeal functions are restored, by means of an implant. With further improvements, this system can alleviate the need for a permanent tracheostomy after total laryngectomy, while maintaining important larynx functions intact. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1669–1673, 2014